IMMUNOHISTOCHEMICAL EXPRESSION OF CD44 IN COLORECTAL CARCINOMA IN RELATION TO HISTOMORPHOLOGIC PARAMETERS AND CLINICO-PATHOLOGICAL FACTORS: A CROSS-SECTIONAL STUDY. - Mishra, Dr. Pragnya Paramita; K, Dr. Madan; Rao, Dr. Anuradha Calicut Kini; Biswas, Dr. Siddhartha; Shetty, Dr. Rohan; Panda, Premanand (Student’s Journal of Health Research Africa, 2024)
Background Cancer stem cells (CSC) have proven to play a vital role in cell invasion, metastasis, and treatment resistance in colorectal carcinoma (CRC), which subsequently led to poor outcomes. Cluster of differentiation 44 (CD44) is usually expressed in stem cells in CRCs and can be detected by immunohistochemistry (IHC). Aims The present study aimed to evaluate the role of immunohistochemical expression of CD44 in CRC cases of this region and its relationship with clinicopathological parameters and patient outcomes. Methods A cross-sectional study included 52 patients with primary CRC who were analyzed for CD44 expression by IHC on paraffin-embedded blocks. Data were collected, tabulated, and statistically analyzed by using SPSS Version 23.0. Results The study had a male predominance (70%) with most participants aged above 45 years (82%). Tumors were predominantly left-sided (69%) and larger than 5 cm (73%). CD44 membranous positivity was found in 78.8% of tumor cells and 59.6% of stromal cells. Signet ring cells showed weak CD44 positivity. CD44 expression correlated with higher tumor stages (T3, T4) and larger tumor sizes (>5 cm), but not with nodal stage, perineural, or lymphovascular invasion. Stromal CD44 positivity was found in 59.6% of cases and showed no significant correlation with tumor stage, size, lymphovascular invasion, perineural invasion, or nodal stage (e.g., T stage: T3 - 14 positive, 16 negative; N stage: N0 - 18 positive, 14 negative; tumor size >5 cm - 21 positive, 17 negative). Conclusions CRC prognosis is independently correlated with CD44 expression, a stem cell marker. They are linked to epithelial-mesenchymal transition (EMT) and tumor budding, with increased expression in high-burden instances. Recommendation Further research should be conducted on the role of CD44 expression in colorectal cancer, particularly focusing on post-neoadjuvant chemotherapy cases, to better understand its prognostic implications and potential as a therapeutic target.